1996
DOI: 10.1046/j.1525-1438.1996.06020085.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial with neoadjuvant chemotherapy in stage IIIB squamous carcinoma cervix uteri: an unexpected therapeutic management

Abstract: A prospective randomized study was carried out in patients with squamous carcinoma of the cervix, stage IIIB. The trial considers the randomization in three different arms: the control group, 53 evaluable patients who were treated with radiotherapy; the neoadjuvant chemotherapy plus radiotherapy group, in which 52 evaluable patients were subjected to the neoadjuvant treatment followed by radiotherapy, and the surgical group which included 50 evaluable patients who were administered neoadjuvant cytostatic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 15 publications
2
31
0
1
Order By: Relevance
“…There are many regimens for neoadjuvant chemotherapy in carcinoma cervix. PVB (cisplatin, vincristine, bleomycin), BOMP (bleomycin, ifosamide, cisplatin), BIP (bleomycine, ifosamide, cisplatin), and a quick VBP regimen were used by different investigators [6,7], and modified VBP regimen consists of (vincristine 1 mg/m 2 on day 1 and cisplatin 50 mg/m 2 on day 1, bleomycin 25 mg/m 2 on day 1 and 2) on weekly basis for three courses [8]. TIP (ifosamide 5 gm/m 2 on day 1, cisplatin 75 mg/m 2 and paclitaxel 175 mg/m 2 on day 3) was given every 3 weeks for a total of three courses [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many regimens for neoadjuvant chemotherapy in carcinoma cervix. PVB (cisplatin, vincristine, bleomycin), BOMP (bleomycin, ifosamide, cisplatin), BIP (bleomycine, ifosamide, cisplatin), and a quick VBP regimen were used by different investigators [6,7], and modified VBP regimen consists of (vincristine 1 mg/m 2 on day 1 and cisplatin 50 mg/m 2 on day 1, bleomycin 25 mg/m 2 on day 1 and 2) on weekly basis for three courses [8]. TIP (ifosamide 5 gm/m 2 on day 1, cisplatin 75 mg/m 2 and paclitaxel 175 mg/m 2 on day 3) was given every 3 weeks for a total of three courses [9].…”
Section: Discussionmentioning
confidence: 99%
“…After three cycles of chemotherapy, downstaging was observed in 50 % of patients. A prospective randomized trial was carried out in patients with squamous cell carcinoma stage IIIB in three different arms-radiotherapy, neoadjuvant chemotherapy followed by radiotherapy, neoadjuvant chemotherapy followed by surgery and whole pelvic irradiation [6]. The overall survival after 4-year follow-up was 37, 53, and 63 % indicating that surgery is the best treatment after NACT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary endpoint of the analysis was survival. In 3 trials (Sardi et al, 1996;Sardi et al, 1998;Benedetti-Panici et al, 2002) patients receiving neoadjuvant chemotherapy followed by surgery demonstrated improved survival compared to those receiving radiotherapy alone. When all 5 trials were combined together, the direction of effect remained significant, with a Hazard Ratio of 0.65 (p = 0.0004) suggesting a 35% reduction in the risk of death and a 14% absolute improvement in survival at 5 years (from 50% to 64%).…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…More importantly perhaps, in the neoadjuvant chemotherapy group, additional pelvic radiotherapy was given to most of the women in two trials [39], [40] and to around 30% of women in another two trials [38]; [41]. This makes it difficult to assess the precise benefit associated with the neoadjuvant chemotherapy plus surgery in comparison with radical radiotherapy.…”
Section: Neoadjuvant Chemotherapy Prior To Radical Surgery Versus Radmentioning
confidence: 99%